Preparation and Superhydrophobicity of Sn Thin Film Based Zn Substrate. Issue 199 (13th June 2019) - Shan, Niu; Chuan, Sun; Bo-Wen, Tang; Junjie, Yan; Yu, Sun; Shu, Wang
Abstract: In this paper, superhydrophobic Sn thin film based on Zn substrate was prepared by simple substitution method. X-ray diffraction analysis was used to determine the chemical composition and structural phase of the film, and the metallographic analyzer was employed to characterize the morphology of Sn film. The results showed that Sn metal and its corresponding Sn/Zn metal oxides formed a special micro/nano composite structure on the surface of Sn thin film. The morphology of Sn film is a composite structure consisting of micro-nano lines and micro-nano particles via the observation. In addition, the water contact angle was used to demonstrate the wettability of the film surface. Specifically, the water contact angle of Sn thin film based on Zn substrate exceeded 150°, which showed its superhydrophobic property. In detail, the influence of the surfactant to achieve a superhydrophobic surface was studied by changing the concentration of each component. By contrast, the best component content for superhydrophobic surface was including 0.02 M SnCl2, 0.01 M diluted sulfuric acid, and 0.05 M stearic acid solution, respectively. It should be mentioned that the superhydrophobicity of metal surface is a very important property of mechanical engineering and structural material, even an application on corrosion protection of metals.